Acquired Perforating Disorder: A Case with Multiple Underlying Diseases - Agnes Rosarina Prita Sari; Monika Puspitasari; Hardyanto Soebono; Niken Trisnowati (Karger Publishers, 2022)
A 51-year-old man came to the dermatology and venereology outpatient clinic with the complaint of multiple itchy lumps on his body. The patient had a previous history of hemodialysis due to end-stage renal disease. He also had a previous history of hepatitis B, an abnormal liver function test, and high blood sugar. Histopathological examination with Masson's trichrome revealed that the patient had extrusion collagen in the epidermis which had invagination. Acquired perforating disorder is frequently misdiagnosed as other skin diseases, thus this condition is underdiagnosed. In addition, underlying diseases frequently associated with acquired perforating collagenosis are chronic kidney disease, hepatic insufficiency, and diabetes mellitus. The patient in this case had all 3 conditions. Further investigation is needed to determine whether acquired perforating disorder with multiple underlying diseases will have similar severity with single underlying disease.